Gender norms and labor-supply expectations: Experimental evidence from adolescents - Elisabeth Grewenig; Philipp Lergetporer; Katharina Werner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Gender gaps in labor-market outcomes often emerge with the arrival of the first child. We investigate a causal link between gender norms and labor-supply expectations within a survey experiment among 2,000 German adolescents. Using a hypothetical scenario, we document that the majority of girls expects to work 20 hours or less per week when having a young child, and expects from their partner to work 30 hours or more. Randomized treatments that highlight the existing traditional norm towards mothers significantly reduce girls' self-expected labor supply and thereby increase the expected gender difference in labor supply between their partners and themselves (the expected within-family gender gap). Treatment effects persist in a follow-up survey two weeks later, and extend to incentivized outcomes. In a second experiment, we highlight another, more gender-egalitarian, norm towards shared household responsibilities and show that this attenuates the expected within-family gender gap. Our results suggest that social norms play an important role in shaping gender gaps in labor-market outcomes around child birth.
Keywords: J16; J22; C93; D83; 330; gender norms; female labor supply; survey experiment